Pengawasan Biaya Operasional pada UD. Saroha Serbelawan - Eko Deswin Miechaels Siringo-ringo; Mega Romauly Tampubolon; Nancy Florida Siagian; Felicia Felicia (Owner : Riset dan Jurnal Akuntansi, 2019)
For companies engaged in providing services, operational costs are a very influential element for the formation of corporate profits. Similarly, the UD. Saroha Serbelawan, so that the management and use of operational costs in this company are always monitored from period to period with a continuous monitoring system to maintain the creation of efficiency and effectiveness of work and to see the responsibility of each part in the deviation that occurs in the use of operational costs. After conducting a review and research on UD. Saroha Serbelawan, it can be seen that in the period of 2004 the company experienced a problem, namely the realization of operating costs in 2004 deviated from a sufficient amount of material from the company's operating budget. " To prove the truth and reality of the company, direct research is carried out in the field to obtain data related to the problem and then conduct library research to obtain theoretical materials as a basis for analyzing and evaluating problems that occur. As for suggestions - suggestions that can be made on the conclusions of the problem that occurs is that in each preparation of operational costs should the company conduct a more careful study of all factors that affect operational costs both internal and external factors and then followed up by increasing supervision of management and use of operational costs, mainly through accounting oversight by creating a more in-company accounting system.